Evaluating the Effects of Educational Multimedia Design Principles on Cognitive Load Using EEG Signal Analysis - Farkish, Araz; Bosaghzadeh, Alireza; Amiri, S. Hamid; Ebrahimpour, Reza (Education and information technologies, 2023)
Educational multimedia has proven to be an effective and efficient way of learning. Designers strive to produce multimedia that convey concepts most efficiently. That is to design multimedia that imposes the least possible cognitive load on the learner. Mayer’s multimedia design principles are well-known, and multiple pieces of research have proven them to be effective. Reviewing the literature makes it obvious that there is a lack of a neurologically supported measure to express the effectiveness of these principles in the enhancement of the learning process. Mayer has reported the importance of these principles through effect sizes of scores obtained from transfer tests taken from the subjects. In this research, we utilized five of the twelve design principles introduced by Mayer to create With-Principles multimedia. These five principles were signaling, coherence, spatial contiguity, temporal contiguity and redundancy. We selected one chapter from Oxford’s open forum 3 and designed two versions of multimedia (With-Principles and Without-Principles) for the chapter. In one version, we designed the multimedia according to the design principles, and in the other version, no specific design principles were applied. A total number of 28 non-native English speaker students were divided into two groups. One group watched the With-Principles version of the multimedia, and the other group watched the Without-Principles version. NASA-TLX and a final comprehension test accompanied the procedure. Meanwhile, the subjects’ brain signals were being recorded. The results from both the post-task tests and the EEG analysis show that the With-Principles multimedia has imposed a significantly lower cognitive load on the learners. Furthermore, we propose the effectiveness of each principle by measuring the amount to which each principle has contributed to reducing the cognitive load of the subjects during the multimedia. Subjects’ brain signals analysis reveals that the signaling and the spatial contiguity principles have the most effect on learning enhancement.